Rhizocorallium hamatum (Fischer-Ooster 1858), a Zoophycos-like trace fossil from deep-sea Cretaceous-Neogene sediments. (3rd April 2017) - Uchman, Alfred; Rattazzi, Bruno
Abstract: Rhizocorallium hamatum (Fischer-Ooster 1858) is a trace fossil of the Zoophycos group, which is distinguished by its mostly horizontal, branched spreite lobes. It has so far, been ascribed mainly to Zoophycos, but the latter should be limited to forms having helical whorls, which are absent in R. hamatum . It has also been ascribed to Phycosiphon, which, however, shows J-shaped spreite lobes, while the lobes of R. hamatum are U-shaped. R. hamatum is very similar to R. commune var. irregulare, but the latter displays a distinctly wider marginal tunnel with respect to lobe width. R. hamatum occurs from the Turonian to Eocene, possibly from the Hauterivian to Oligocene, but mostly from Maastrichtian to Palaeocene, deep sea, mainly turbiditic sediments rich in marl. The tracemaker, probably a 'worm'-like invertebrate, ingested an organic-rich mud of the background sediment and relocated it into the middle to deep tiers within the underlying turbiditic marl, mostly in form of faecal pellets packed within the spreite lobes, for further use as a food resource. This way of feeding was a response to food deficiency on the deep-sea floor.